Innovation of Electronic Card-Based Public Transportation Fare Payment Systems - Narimawati, Umi; Aprilia, C; Febriana, I R; Juliana, Rilla Bunga; Jumansyah, Rizky; Saputra, Herry; Albar, Chepi Nur; Fahrezi, Muhammad (International Journal of Research and Applied Technology (INJURATECH), 2023)
The development of technology is increasingly rapid, encouraging the people of Indonesia, especially Bandung city, to start shifting from cash to the era of a cashless society, especially when it is currently in the Covid-19 pandemic. This research aims to design the concept of electronic services for transportation in Bandung. The method used was descriptive to 25 respondents. These results indicated that the Bandung communities need the latest innovations to simplify the payment system. The use of the EBAP Card is only by using a card that is attached to a sensor machine provided by public transportation. EBAP Card is made as a substitute for cash for public transportation payment transactions. This EBAP Card payment transaction is faster than using cash. The direct impact of this program's benefits for the community is that the public can pay public transport fares with an EBAP Card that is safe, comfortable, accurate, and efficient. This payment system will reduce direct contact during this Covid-19 period. With the implementation of electronic-based payments, payment transaction services on public transportation are faster, so it is hoped that the travel convenience of public transport users in Bandung will increase.